Validation of the Proposed Clinical Diagnostic Criteria of Enteric Fever - Neopane, A; Panta, S (Kathmandu University Medical Journal, 2014)
Background Enteric fever is very common infectious disease in developing countries like Nepal. Due to lack of resources diagnosis has to be clinical most of the time. Hence a proposal of clinical diagnostic criteria and validation of the same would be very useful. Objective To validate the proposed clinical diagnostic criterion including features characterized as major and minor criteria Methods This study was done in the department of medicine of Kathmandu Medical College Teaching hospital, from June 2009 to January 2012. A total of 114 patients presenting with fever were included in the study. After proposal of clinical diagnostic criteria for enteric fever, by a prior published study, all the fever patients were grouped according to criteria positive or negative. The most significant criteria were validated by calculating sensitivity and specificity along with positive and negative likelihood ratios with blood culture taken as gold standard. Results A total of 114 patients were enrolled. Total patients diagnosed as enteric was 47.3 %. Clinical diagnostic criterion B which included three major (headache, fever and relative bradycardia) and three minor criteria (abdominal pain, vomiting, diarrhea, splenomegaly and chills) was highly significant (p=<.0001) in diagnosing enteric fever and had a sensitivity of 72.2% ( 95% CI 58.1- 83.1) and specificity of 98.3% ( 95% CI 89.8-99-9). The positive likelihood ratio was 43.33 (95 % CI 6.16-304.77) and negative likelihood ratio as 0.28 (95% CI 0.18-0.43). Conclusion Clinical diagnostic criteria can be a very useful tool for diagnosis of enteric fever when culture facility is not available. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10986 Kathmandu Univ Med J 2012;10(4):8-11